Administrative professional : theories and procedures - Stulz, Karin. 4 0 16; 1967- Shumack, Kellie Ann,;Fulton-Calkins, Patsy; 5 (Andover : Cengage Learning, 2015)
Emphasises on critical thinking, creative problem solving, and professional development preparing students for challenges they may face in global market place. This title offers coverage of key topics ranging from various technologies, the changing workplace, leadership, and personal finance
The Workplace--Constantly Changing -- Your Professional Image -- Workplace Teams -- Self-Management -- Ethical Theories and Behaviors -- Leadership -- Customer Service -- Written Communication -- Verbal Communication and Presentations -- Global Communication--Technology and Etiquette -- Managing Records -- Managing Electronic Records -- Personal Finance and Investment Strategies -- Meeting and Event Planning -- Travel Arrangements -- Workplace Mail and Copying -- Job Search and Advancement
Includes bibliographical references and index
Keywords: 2 -- 0; 6; Office practice;Secretaries -- 20; 20; 2